Ghrelin accelerates growth of olfactory ensheathing cells through ERK pathway - ZHANG, PEI; RUIFENG, L I; HUICHENG, L V; TONG, YANXIANG; CHANG, ZHIQIANG; BAOLONG, Y U; YIMIN, W U (The Indian Journal of Animal Sciences, 2016)
Ghrelin, an endogenous ligand for the growth hormone secretagogue receptor (GHSR), stimulates growth hormone (GH) secretion and has both orexigenic and adipogenic effects. This study sought to understand the potential involvement of MAPKs in ghrelin-induced growth of OECs. Different concentrations of ghrelin were applied to cultured OECs to observe the growth rate of cells and changes in phosphorylation state of MAPKs ERK1/2, JNK and p38. Ghrelin-induced OECs growth was promoted primarily by phosphorylated ERK1/2, and that this phosphorylation, as well as p90rsk phosphorylation, was mediated by the ghrelin receptor GHSR. In conclusion, our study suggested that ghrelin promotes the growth of OECs primarily through the ERK pathway.